2018
DOI: 10.3329/jbau.v16i1.36486
|View full text |Cite
|
Sign up to set email alerts
|

Profitability analysis of paddy production: A case of agricultural zone 1, Niger State Nigeria

Abstract: This study estimated the profitability of rice production among small scale farmers in Bida agricultural zone of Niger state. The study utilized a multi-stage random sampling technique to select a total of one hundred and five (105) rice farmers in the area. The data was collected through a well-structured questionnaire from four communities in the study area. Descriptive statistics and farm budgeting tools were used for the analyses. The descriptive analysis showed that the farmers are highly productive betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 3 publications
2
16
1
Order By: Relevance
“…27.35% in overall. The gross profit ratio obtained was lower than the gross profit obtained in Nigeria state, which was 0.45 (Bwala & John, 2018).…”
Section: Return From Productioncontrasting
confidence: 60%
See 1 more Smart Citation
“…27.35% in overall. The gross profit ratio obtained was lower than the gross profit obtained in Nigeria state, which was 0.45 (Bwala & John, 2018).…”
Section: Return From Productioncontrasting
confidence: 60%
“…Gross margin = Gross return -Total variable cost Where, Gross return = Price × total quantity marketed Total variable cost = Summation of cost incurred in all the variable items Similarly, Gross Profit Ratio (GPR) = Gross Margin / Total Revenue (Bwala & John, 2018).…”
Section: Gross Marginmentioning
confidence: 99%
“…This observation reflects the trend presented in Table 1 where most farmers are young, energetic, and economically active to get involved in rice production. In addition, young farmers are believed to easily accept and adopt new technologies and extension services to facilitate rice production [16], contrary to older farmers who are relatively rigid on accepting new technology [20]. The significant numbers of farmers are married which is beneficial for agricultural activities.…”
Section: Socio-economic Characteristicsmentioning
confidence: 99%
“…The net return obtained was N 92,697.00 ha -1 by small scale farmers in Kadawa and N 122,547.00 ha -1 by farmers in Watara in the Sudan savanna ecological zone [7]. Madu and Aniobi [8] in their study revealed that the variable cost per hectare for rice production was found to be $360.29 (N 162,130.5) per production cycle, while total revenue of $650 (N292,500.00|) was realized by the respondents. Meanwhile, the gross margin and gross profit were estimated to be $289.71 (N130, 369.50) and $281.56 (N 126,702.00), respectively.…”
Section: Introductionmentioning
confidence: 99%